Determination of Chromite Sands Suitability for Use in Moulding Sands - Stec K.; Podwórny J.; Psiuk B.; Kozakiewicz Ł. (Archives of Foundry Engineering, 2017)
Using the available analytical methods, including the determination of chemical composition using wavelength-dispersive X-ray fluorescent spectroscopy technique and phase composition determined using X-ray diffraction, microstructural observations in a highresolution scanning microscope equipped with an X-ray microanalysis system as well as determination of characteristic softening and sintering temperatures using high-temperature microscope, the properties of particular chromite sands were defined. For the study has been typed reference sand with chemical properties, physical and thermal, treated as standard, and the sands of the regeneration process and the grinding process. Using these kinds of sand in foundries resulted in the occurrence of the phenomenon of the molding mass sintering. Impurities were identified and causes of sintering of a moulding sand based on chromite sand were characterized. Next, research methods enabling a quick evaluation of chromite sand suitability for use in the preparation of moulding sands were selected.